Field evaluation of a multiplex real-time reverse transcription polymerase chain reaction assay for detection of Vesicular stomatitis virus - Wilson, William (2009)
Sporadic outbreaks of vesicular stomatitis (VS) in the United States result in significant economic losses for the U.S. livestock industries because VS is a reportable disease that clinically mimics foot- and-mouth disease. Rapid and accurate differentiation of these 2 diseases is critical because their consequences and control strategies differ radically. The objective of the current study was to field validate a 1-tube multiplexed real-time reverse transcription polymerase chain reaction (real-time RT-PCR) assay for the rapid detection of Vesicular stomatitis New Jersey virus and Vesicular stomatitis Indiana virus strains occurring in Mexico and North and Central America. A comprehensive collection of 622 vesicular lesion samples obtained from cattle, horses, and swine from throughout Mexico and Central America was tested by the real-time RT- PCR assay and virus isolation. Overall, clinical sensitivity and specificity of the real-time RT-PCR were 83% and 99%, respectively. Interestingly, VS virus isolates originating from a specific region of Costa Rica were not detected by real-time RT-PCR. Sequence comparisons of these viruses with the real-time RT-PCR probe and primers showed mismatches in the probe and forward and reverse primer regions. Additional lineage-specific primers and a probe corrected the lack of detection of the missing genetic lineage. Thus, this assay reliably identified existing Mexican and Central American VS viruses and proved readily adaptable as new VS viruses were encountered. An important secondary result of this research was the collection of hundreds of new VS virus isolates that provide a foundation from which many additional studies can arise.